The journey to Cuernavaca, Mexico, by John Holt and his relevance for the history of Global Movement of Homeschooling (Práxis Educativa, 2020)
This article studies the impact that the different trips to Cuernavaca (Mexico) have on John Holt at the beginning of the 1970s. Those trips were relevant to the development of his ideas about educational institutions and to the genealogy of the homeschooling movement. The time spent by Holt at the Intercultural Documentation Center (CIDOC) in Cuernavaca meant the personal encounter with Ivan Illich. It was then that he came into contact with the ideas of de-schooling. These ideas are the basis of the turn that led Holt thereafter to explore educational alternatives outside the scope of the school institutions and that made him position himself as one of the outstanding leaders of homeschooling/unschooling in the United States. This research analyzes Holt's trips to Cuernavaca and his stays at the CIDOC of Ivan Illich from primary historical sources.Keywords: John Holt. Ivan Illich. Homeschooling.